Immune regulation and organ damage link adiponectin to sepsis - Zhang, Lili; Lin, Yuning; Zhang, Zhongying; Chen, Yuting; Zhong, Jinqing (Frontiers in Immunology, 2024)
Sepsis is a life-threatening syndrome characterized by organ dysfunction, resulting from an uncontrolled or abnormal immune response to infection, which leads to septicemia. It involves a disruption of immune homeostasis, marked by the release of Inflammatory factors and dysfunction of immune cells. Adiponectin is widely recognized as an anti-inflammatory mediator, playing a crucial role in regulating immune cell function and exerting protective effects on tissues and organs. However, the physiological role of adiponectin in septicemia remains unclear due to the condition’s association with immune response dysregulation and organ damage. This study focuses on the potential relationship between adiponectin and excessive immune responses, along with organ injury in septicemia. Additionally, we investigate possible explanations for the observed discrepancies in adiponectin levels among critically ill or deceased patients compared to theoretical expectations, aiming to provide valuable insights for clinical diagnostics and therapeutic interventions in sepsis.